2010
DOI: 10.1016/j.devcel.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Transitions in Germ Cell Development and Meiosis

Abstract: Germ cell development is controlled by unique gene expression programs and involves epigenetic reprogramming of histone modifications and DNA methylation. The central event is meiosis, during which homologous chromosomes pair and recombine, processes that involve histone alterations. At unpaired regions, chromatin is repressed by meiotic silencing. After meiosis, male germ cells undergo chromatin remodeling, including histone-to-protamine replacement. Male and female germ cells are also differentially marked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
181
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(187 citation statements)
references
References 101 publications
0
181
1
5
Order By: Relevance
“…55 In male mouse fetuses, PGCs differentiate into prospermatogonia, enter mitotic arrest and reestablish methylation starting at E15; this is the time point at which paternal sex-specific imprints are set. 56,57 Consequently, this window is especially important for disruptions to loci that escape demethylation as well as resetting of global methylation in male offspring with any effects likely to be seen in the F2 generation. 33,58 Non-mammalian animals, in general, do not have imprinted genes.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…55 In male mouse fetuses, PGCs differentiate into prospermatogonia, enter mitotic arrest and reestablish methylation starting at E15; this is the time point at which paternal sex-specific imprints are set. 56,57 Consequently, this window is especially important for disruptions to loci that escape demethylation as well as resetting of global methylation in male offspring with any effects likely to be seen in the F2 generation. 33,58 Non-mammalian animals, in general, do not have imprinted genes.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Male germ cells undergo stem cell self-renewal, mitotic divisions in spermatogonial proliferation, genomic rearrangement by meiotic homologous recombination at the spermatocyte stage, and morphological changes of round spermatids into elongated spermatids to form mature spermatozoa (1)(2)(3). During spermiogenesis, nucleosomal histone proteins are replaced with transition nuclear proteins (TNPs) and subsequently, protamines, the major nucleosomal proteins in spermatozoa.…”
mentioning
confidence: 99%
“…Meiosis is the cornerstone of sexual reproduction, as it generates haploid cells (gametes or spores) required for the formation of a diploid organism genetically distinct from both parents. 55 Substantial chromatin changes, including modifications of histones, are observed prior to and during meiosis, as well as during the maturation of gametes (gametogenesis). 55 A yeast strain specifically impaired in ubiquitylation of H2B (through mutation of the target lysine to arginine, K123R) was found to be unable to form spores on account of meiotic prophase arrest.…”
Section: H2bub1 In Gametogenesismentioning
confidence: 99%
“…55 Substantial chromatin changes, including modifications of histones, are observed prior to and during meiosis, as well as during the maturation of gametes (gametogenesis). 55 A yeast strain specifically impaired in ubiquitylation of H2B (through mutation of the target lysine to arginine, K123R) was found to be unable to form spores on account of meiotic prophase arrest. 7 Detailed characterization of the H2B K123R mutant in a rapidly sporulating genetic background revealed that the formation of double-stranded breaks (DSBs) during meiotic pachytene is delayed, and the frequencies of DSBs at certain loci were reduced.…”
Section: H2bub1 In Gametogenesismentioning
confidence: 99%